(untitled) (Journal of Comparative Social Work, 2025)
Gender-Based Violence (GBV) remains a significant health and social issue in Tanzania and Africa at large. Most GBV reduction interventions often concentrate on mitigating harmful cultural practices perpetuating it, therefore failing to identify and integrate aspects of the indigenous norms perceived to be protective to women against GBV. Thus, adopting qualitative approaches and cross-sectional design, this article: (i) explores norms considered protective to women against GBV in studied communities and the attached values; (ii) identifies and presents the tensions that emerge in the application of such norms when viewed through the analytical lens of the conventional frameworks that protect human and women rights and freedom against discrimination and abuse; and (iii) highlight potentials for the integration of these norms into social work practice to promote culturally sensitive interventions. Findings indicate varied views regarding GBV prevalence and magnitude. They also confirm the presence of deep-seated beliefs among the community members regarding the existence of some cultural norms that they perceived to be protective of women from GBV. Irrespective of this reality, findings also show tensions and clashes between some aspects of norms and human rights conventional frameworks and social work ethics on diversity and inclusion. Mindful of the importance of the integration of contextually relevant and culturally appropriate knowledge into social work, the study establishes the need for social workers to adopt a culturally sensitive and reflective mindset when designing gender-based interventions by sorting out what norms can be kept and what can be discarded.